Adult‐onset primary cyclic autoimmune neutropenia: a case report. Issue 4 (5th February 2018) - Yabushita, Tomohiro; Hiramoto, Nobuhiro; Ono, Yuichiro; Yoshioka, Satoshi; Karakawa, Shuhei; Kobayashi, Masao; Ishikawa, Takayuki
Abstract : BACKGROUND: A few cases of primary autoimmune neutropenia (AIN) have been reported in adults, but cyclic primary AIN, which is characterized by the periodic oscillation of neutrophils, is uncommon in adults. STUDY DESIGN AND METHODS: Herein, we report a 70‐year‐old man referred to our hospital with severe neutropenia and thrombocytopenia. He had experienced intermittent episodes of low‐extremity purpura for the past 3 months, with cellulitis on the skin of the scalp 1 month previously. RESULTS: The patient presented with severely low neutrophil and platelet (PLT) counts. Myeloid progenitors and megakaryocytes were increased in the marrow, but mature neutrophils were remarkably decreased. Anti‐neutrophil antibodies to specific epitopes were detected at neutropenia. Based on these findings, AIN accompanied by autoimmune thrombocytopenia was diagnosed. The patient experienced synchronous fluctuations of neutrophil and PLT counts three times. Despite no treatment, the neutrophil count fluctuated within the range of 0.06 × 10 9 to 1.65 × 10 9 /L, and the PLT count fluctuated from 0.7 × 10 10 to 20.5 × 10 10 /L. We identified an inverse relationship between neutrophil count and anti‐neutrophil antibody titers, establishing the conclusive diagnosis of cyclic AIN. After prednisolone treatment, the neutrophil and PLT counts normalized, and the patient has maintained long‐term remission. CONCLUSION: We report a rare case of cyclic AIN diagnosed from the inverse association between periodic oscillation of anti‐neutrophil antibody titers and neutrophil counts. This clinical course suggests that in AIN patients, laboratory data and recurrent signs of infection should be monitored regularly, including shortly after neutrophil recovery.